Evaluation of the effects of epidural labour analgesia on mode of delivery - Khatun, Marufa; Rahim, M. Abdur; Rahman, Fatema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Epidural analgesia is the most effective method of pain relief during labour and the only method that provides complete analgesia without maternal or foetal adverse effects. This study aimed to assess the mode of delivery outcomes of labour in women who had received effective epidural analgesia. Methods: After ethical approval, this quasi-experimental study was carried out in Dhaka Medical College Hospital for one year, from July 2021 to June 2022. A total of 100 admitted pregnant women (37 weeks to 41 weeks) in the labour ward were included in the study according to the inclusion and exclusion criteria. Among them, 50 women were in group A (with epidural analgesia), and the other 50 were in group B (without epidural analgesia). A detailed history and thorough clinical examination were carried out on each patient. Data were collected in separate case-record forms and analyzed using SPSS 24. Results: Mean age, gestational age, parity, and body mass index were statistically similar in both group A and B. Normal vaginal delivery rate (86% vs. 90%), instrumental delivery rate (10% vs. 6%), and caesarean section rate (4% vs. 4%) were not significantly different in both groups. Besides, both group A and B had statistically similar APGAR scores at 1st (8.66±0.87 and 8.80±0.83 respectively, p=0.414) and 5th min (9.66±0.68 and 9.74±0.59 respectively, p=0.537). Conclusions: Epidural labour analgesia can be safely recommended as a method of labour analgesia, provided the prerequisites are fulfilled. It has no significant adverse effect on the mode of delivery.